The Surface Heat Flow of Mars at the Noachian–Hesperian Boundary - Javier Ruiz; Laura M. Parro; Isabel Egea-González; Ignacio Romeo; Julia Álvarez-Lozano; Alberto Jiménez-Díaz (Remote Sensing)
The time period around the Noachian–Hesperian boundary, 3.7 billionyears ago, was an epoch when great geodynamical and environmental changes occurred on Mars. Currently available remote sensing data are crucial for understanding the Martian heat loss pattern and its global thermal state in this transitional period. We here derive surface heat flows in specific locations based on the estimations of the depth of five large thrust faults in order to constrain both surface and mantle heat flows. Then, we use heat-producing element (HPE) abundances mapped from orbital measurements by the Gamma-Ray Spectrometer (GRS) onboard the Mars Odyssey 2001 spacecraft and geographical crustal thickness variations to produce a global model for the surface heat flow. The heat loss contribution of large mantle plumes beneath the Tharsis and Elysium magmatic provinces is also considered in our final model. We thus obtain a map of the heat flow variation across the Martian surface at the Noachian–Hesperian boundary. Our model also predicts an average heat flow between 32 and 50 mW <semantics>m−2</semantics>, which implies that the heat loss of Mars at that time was lower than the total radioactive heat production of the planet, which has profound implications for the thermal history of Mars.